2008
DOI: 10.1017/s0022215107001612
|View full text |Cite
|
Sign up to set email alerts
|

Does hormone replacement therapy in post-menopausal women have any effect upon nasal physiology?

Abstract: Female hormone replacement therapy has no discernable effect upon nasal physiology and should not be considered a cause of rhinitic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
10
0
3
Order By: Relevance
“…Some studies have reported that nasal physiology and smell sensitivity are influenced by the menstrual cycle phases, pregnancy or hormone contraceptives [3,[20][21][22]. However, more recent publications could not find significant differences in olfactory function between women with different hormonal status [23][24][25]. The mechanisms by which sexual hormones influence the sense of smell are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that nasal physiology and smell sensitivity are influenced by the menstrual cycle phases, pregnancy or hormone contraceptives [3,[20][21][22]. However, more recent publications could not find significant differences in olfactory function between women with different hormonal status [23][24][25]. The mechanisms by which sexual hormones influence the sense of smell are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously, hormone-replacement ther apy did not result in the improvement of nasal airway dimensions, mucociliary clearance or rhinitis quality of life questionnaire scores in postmenopausal women [51]. However, postmenopausal women who received 8 months of either oral or transdermal patch hormone therapy (estrogen and progesterone) demonstrated lower airway resistance, decreased olfactory thresholds and greater olfactory sensitivity [84].…”
Section: Hormonal Replacementmentioning
confidence: 52%
“…It has been established that progesterone and estrogen receptors are present in the nasal mucosa and that the number of estrogen b-receptor-positive cells in the mucosal glands correlate with nasal symptoms [50]. Although withdrawal of estrogen is thought to have atrophic effects on nasal mucosa, no change was found in a number of physiologic parameters with hormone therapy, either for replacement therapy or for in vitro fertilization [51,52].…”
Section: Hormonal Rhinitismentioning
confidence: 99%
“…По данным литерату ры, ухудшение носового дыхания и обоняния может отмечаться при использовании гормональных кон трацептивов [8,17]. Наряду с этим применение про гестерона и глюкокортикоидов при изменении гор монального статуса у беременных, а также замести тельная гормональная терапия у пациенток в пост менопаузе не выявили заметного влияния на разви тие симптомов ринита [18,19].…”
Section: The Prevalence and Clinical Features Of Hormonal Rhinitis (аunclassified